Effects of a thermally stable chlorophyll extract from diatom algae on surface textured Si solar cells. Issue 44 (16th May 2015) - Chen, Chiang-Ting; Hsu, Fang-Chi; Huang, Jeng-Yeh; Chang, Chi-Yuan; Chang, Tsung-Yuan; Lin, Hsiu-Mei; Lin, Tai-Yuan; Chen, Yang-Fang
<x xml:space="preserve">Abstract</x> We present the effects of a chlorophyll extract from diatom algae as a spin-coating anti-reflection layer on surface textured silicon solar cells.